Synthesis and Antimicrobial Evaluation of N-Substituted-5- Benzylidene-2,4-Thiazolidinedione Derivatives: Synthesis of N-substituted-5-benzylidene-2,4-thiazolidinediones - Neeru Malik,; D.N. Prasad, (Iranian Journal of Pharmaceutical Sciences, 2012)
A series of N-substituted-2,4-thiazolidinedione derivatives (TZDs) were prepared via N-alkylation of 2,4-TZD at position 3 using substituted benzyl halides. Synthesized N-substituted-2,4-TZD was then substituted at position 5 with substituted aromatic aldehyde according to Knoevenagel condensation method. Structures of the compounds were elucidated using various spectral techniques viz. IR, 1HNMR. The synthesized compounds were evaluated for their antimicrobial activity.